A flow-leak correction algorithm for pneumotachographic work-of-breathing measurement during high-flow nasal cannula oxygen therapy. (April 2018) - Montecchia, Francesco; Midulla, Fabio; Papoff, Paola
Highlights: Work of breathing (WOB) is hard to measure during high-flow nasal cannula (HFNC). A monitoring facemask and pneumotachograph simplifies the task apart from leakages. A leak-correction algorithm allows WOB measurement via pneumotachography during HFNC. Tested on a mechanical lung model and in vivo our system reliably computed WOB. Abstract: Measuring work of breathing (WOB) is an intricate task during high-flow nasal cannula (HFNC) therapy because the continuous unidirectional flow toward the patient makes pneumotachography technically difficult to use. We implemented a new method for measuring WOB based on a differential pneumotachography (DP) system, equipped with one pneumotachograph inserted in the HFNC circuit and another connected to a monitoring facemask, combined with a leak correction algorithm (LCA) that corrects flow measurement errors arising from leakage around the monitoring facemask. To test this system, we used a mechanical lung model that provided data to compare LCA-corrected respiratory flow, volume and time values with effective values obtained with a third pneumotachograph used instead of the LCA to measure mask flow leaks directly. Effective and corrected volume and time data showed high agreement (Bland–Altman plots) even at the highest leak. Studies on two healthy adult volunteers confirmed that corrected respiratory flow combined with esophageal pressure measurements can accurately determine WOB (relative error < 1%). We conclude that during HFNC therapy, a DP system combined with a facemask and an algorithm that corrects errors due to flow leakages allows pneumotachography to measure reliably the respiratory flow and volume data needed for calculating WOB.